THE EFFECTIVENESS OF COOPERATIVE LEARNING METHODS IN IMPROVING EXTRACURRICULAR SOCCER SKILLS - Ramdani Umar; Muhammad Salahuddin; Armin Haluti (JURNAL PENDIDIKAN GLASSER, 2025)
Enhancing the quality of learning in extracurricular activities, particularly in football, is essential for developing students’ technical skills and character at the senior high school level. This study aims to evaluate the effectiveness of the cooperative learning method in improving students’ technical football skills in the extracurricular program at SMA Negeri 1 Luwuk. A mixed-method approach was employed, combining quantitative and qualitative designs. Data were collected through observations, skill tests (pre-test and post-test), and interviews with students and coaches. The sample consisted of 30 students selected purposively. The results showed that the implementation of cooperative learning significantly improved students’ passing, dribbling, and shooting abilities. Qualitatively, students also demonstrated increased motivation, collaboration, and active participation during the learning process. These findings reinforce the theory that cooperative learning is effective in developing both motor and social skills, particularly in team sports. This study contributes practical insights for designing extracurricular training programs and enriches theoretical perspectives on active learning in physical education. The conclusion emphasizes that cooperative learning is an effective strategy for improving students’ football skills. Future research is recommended to explore its application in other sports contexts and over longer training durations